Effect of Structural Relaxation on the Indentation Size Effect and Deformation Behavior of Cu–Zr–Based Nanoglasses - Sharma, A; Nandam, Sree Harsha; Hahn, Horst; Prasad, K. Eswar (Frontiers in Materials, 2021)
In this work, the deformation behavior of as processed (AP) and structurally relaxed (SR) Cu-Zr based nanoglasses (NGs) is investigated using nano- and micro-indentation. The NGs are subjected to structural relaxation by annealing them close to the glass transition temperature without altering their amorphous nature. The indentation load, P vs. displacement, h curves of SR NGs are characterized by discrete displacement bursts while the AP samples do not show any of them suggesting that the annealing has caused local change in the amorphous structure, thereby leading to flow localization. In both the samples, the hardness (at nano and micro-indentation) decreases with increasing P demonstrating the indentation size effect. The micro-indentation imprints of SR NG show evidence of shear bands at the periphery indicating heterogeneous plastic flow while AP NG do not show any shear bands. Interestingly, the shear band density decreases with P highlighting the fact that plastic strain is completely accommodated by the shear bands in the sub-surface deformation zone. The results are explained by the differences in amorphous structure of the two NGs.